A simple noninvasive model to predict significant fibrosis in children with chronic hepatitis B. Issue 25 (25th June 2021) - Zhang, Kang-Ling; Chen, Xiu-Qi; Lv, Zi-Li; Tang, Qing; Shan, Qing-Wen
Abstract : Abstract: To develop a noninvasive model to predict significant fibrosis in children with chronic hepatitis B (CHB). A total of 116 CHB pediatric patients who underwent liver biopsy were included in the study. Liver histology, which is the gold standard for assessing fibrosis, was performed. Blood routine examination, coagulation function, liver biochemistry, viral serology, and viral load were analyzed. Receiver operating characteristic curve analysis was used to analyze the sensitivity and specificity of all possible cut-off values. Based on the correlation and difference analyses, 7 available clinical parameters (total bile acid, gamma-glutamyl transpeptidase [GGT], aspartate transaminase, direct bilirubin to total bilirubin ratio, alanine aminotransferase, prealbumin [PA], and cholinesterase) were included in the modeling analysis. A model to predict significant liver fibrosis was derived using the 2 best parameters (PA and GGT). The original model was . After the mathematical calculation, the G index=600 × GGT/PA 2 predicted significant fibrosis, with an area under the receiving operating characteristics (AUROC) curve of 0.733, 95% confidence interval (0.643–0.811). The AUROC of the G index (0.733) was higher than that of aminotransferase to platelet ratio index (APRI) (0.680) and Fibrosis index based on 4 factors (FIB-4) (0.601) in predicting significant fibrosis in children with CHB. If the values of the G index were outside the range of 0.28 to 1.16, 52% of children with CHB could avoid liver biopsy, with an overall accuracy of 75%. The G index can predict and exclude significant fibrosis in children with CHB, and it may reduce the need for liver biopsy in children with CHB.